Translating Cultures: A Study of U.R. Ananthamurthy’s Samskara in English and Beyond - Shrusti Patil (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
This paper examines the politics and poetics of translation through a case study of U. R. Ananthamurthy’s Samskara (1965) and its influential English translation by A. K. Ramanujan (1976). Written originally in Kannada, Samskara interrogates Brahmin orthodoxy, ritual practice, and ethical dilemmas within a caste-bound society. Its translation into English enabled the novel’s circulation beyond regional borders, situating it within postcolonial, comparative, and world literature discourses. By analyzing Ramanujan’s translation strategies-particularly his retention of culturally specific terms and his balancing of readability with cultural integrity-the paper highlights how Samskara travels across languages without erasing its rootedness. Drawing on theories of translation by Lawrence Venuti, GayatriChakravortySpivak, and Walter Benjamin, the discussion foregrounds translation as a process of cultural negotiation rather than mere linguistic transfer. The paper argues that Samskara in translation exemplifies the transformative potential of Indian literatures in global circulation, showing how regional texts acquire new meanings and afterlives in diverse cultural contexts.